ANALISIS TITIK IMPAS USAHATANI KENTANG DI DESA MANEMBO KECAMATAN PASSI TIMUR BOLAANG MONGONDOW - Sulu, Claudio Junito; Ruauw, Eyverson; Sondakh, Mex Frans Lodwyk (AGRI-SOSIOEKONOMI, 2022)
The purpose of this research was to analyze the break even point of potato farming in Manembo Village, East Passi District. This research was carried out for three months from July 2021 to September 2021. The data used in this study were primary data and secondary data then descriptively analyzed. The results showed that at the prevailing price level and the production results achieved, potato farmers in Manembo Village earned an income of IDR 5,105 256 in one planting. The break-even point (BEP value) of potato farming in one planting in Manembo Village was achieved at a value of IDR 2,529 /kg. The amount of production that must be obtained by potato farmers in Manembo Village in order to break even is 57 sacks at a price level of Rp. In other words, the minimum price of Potatoes in Manembo Village is Rp. 2.529 at a production level of 26.47 kg. Production can be increased by carrying out more intensive management of potato farming.